Implementation of Independent Curriculum Through Project Based Learning Model to Improve Students' Creativity at Sma Frater Don Bosco Manado - Sadsuitubun, Marisca A. B.; Sumual, Tinneke Evie Meggy; Krowin, Marthinus M. (Abdurrauf Science and Society, 2025)
This study aims to analyze the implementation of the Independent Curriculum through the Project Based Learning (PBL) learning model at SMA Frater Don Bosco Manado and identify the problems faced by teachers in the implementation process. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of PBL has provided space for students to increase creativity through contextual projects, although there are still challenges in student independence, time management, and assessment mechanisms. The conclusion of this study is that PBL can be an effective strategy to implement the Independent Curriculum optimally, with the note that there is increased support for teachers and students.